Città storica e sostenibilità / Historic Cities and Sustainability - De Vita, Maurizio (Strumenti per la didattica e la ricerca, 2012)
A subject that is inexplicably little studied at present, or indeed not at all, is that of the quest for possible applications and feasible objectives in the energy requalification of existing buildings, existing or planned open spaces, old city centres and the monumental and diffuse cultural heritage. At the present time it is crucial that the issues, research and techniques linked to the possibilities of an aware use of energy are applied to the old city centres and the existing heritage. This must start from a knowledge and investigation of the traditional building materials and techniques, which are in themselves inherently sustainable (comprising both the ancient city and the consolidated modern city and their historic stratifications). The historic environment indeed represents an infinite cultural and environmental resource and a very high percentage of the global architectural heritage.